The Influence of Work Motivation, Work Environment, and Professionalism on Employee Performance at Darul Hasanah Foundation, Semarang City - Jamila, Adroul; Oktarina, Nina (Majapahit Journal of Islamic Finance and Management, 2025)
The purpose of this study is to analyze the influence of work motivation, work environment and professionalism on employee performance at Yayasan Darul Hasanah Semarang Regency. All employees were involved as respondents with a total of 65 people. In this study using quantitative survey method and the type of primary data used in the form of questionnaires distributed with saturated sample technique, as well as secondary data sourced from interviews, journals and books. The software used is IBM SPSS 26 using the multiple linear analysis method. The results of this study indicate that work motivation has a positive and significant effect on employee performance with a significance value of 0.000 <0.05 with t value of 5.795> 0.678 t table. The work environment has a positive and significant effect on employee performance with a significance value of 0.014 <0.05, and a t value of 2.530> 0.678 t table. Professionalism has a positive and significant effect on employee performance with a significance value of 0.019 <0.05, with t value 2.416> 0.678 t table. Work motivation, work environment, and professionalism variables have a positive and significant influence on employee performance with a value of f count 28.545 > f table 2.746.